The Effect of Return on Assets to Profit Growth of Perumda BPR Garut - Ayu Siti Nurhaida; Nurhasanah (Fakultas Ilmu Sosial dan Ilmu Politik - Universitas Garut, 2022)
This research is motivated by changes in profit growth that are still unstable at Perumda BPR Garut, which tend to be high and fluctuate in company activities. Return on Assets (ROA) can be a factor driving profit growth. This study aims to determine the influence of ROA on Profit Growth at Perumda BPR Garut. The data used in this study comes from the financial services authority. In using the data, the researcher uses a quantitative method where the researcher focuses on the analysis of causal relationships. The data taken is in the form of secondary data. Data collection techniques were carried out in this study using documentation and a literature study with descriptive and statistical data analysis. The results of this study indicate that during the 2015-2021 period, ROA and Profit Growth at Perumda BPR Garut fluctuated. Tests carried out using simple linear regression resulted in a relationship correlation value of return on asset is interpreted to have a strong relationship level toward profit return at Perumda BPR Garut. With a coefficient of determination of 0.748, this value implies that the effect of return on assets on profit growth is 74.8%, while the remaining 25.8% is influenced by other variables not examined. Keywords: Return on Assets; Profit Growth; Financial Management